2013
DOI: 10.1016/j.ejvs.2012.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Autologous Lymph-node Transplantation for Limb Lymphoedema

Abstract: ALNT may engender severe, chronic complications, particularly persistent iatrogenic lymphoedema. Further investigations are required to evaluate and clearly determine its indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
144
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(148 citation statements)
references
References 21 publications
1
144
1
2
Order By: Relevance
“…25,26 In contrast, the connections between lymphatics and nearby veins in LVA procedures typically are superficial and require only a fraction of the lymphatics in the affected limb. In this series, we opted for VLNT over LVA in patients with upper extremity lymphedema because we believed that the risk of donor site lymphedema may be lower when harvesting from the groin compared with the axilla or chest wall.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 In contrast, the connections between lymphatics and nearby veins in LVA procedures typically are superficial and require only a fraction of the lymphatics in the affected limb. In this series, we opted for VLNT over LVA in patients with upper extremity lymphedema because we believed that the risk of donor site lymphedema may be lower when harvesting from the groin compared with the axilla or chest wall.…”
Section: Discussionmentioning
confidence: 99%
“…However, one study reported a small change in the postoperative lymphoscintigraphies in donor site legs, and another study described new-onset lymphedema in donor limbs. 40,41 Intraoperative laser imaging of lymph nodes with indocyanine green dye can guide selective VLNT lymph node collection. Sentinel lymph node mapping of donor sites with technetium tracer and the collection of lymph nodes other than the sentinel nodes can further improve safety (Fig.…”
Section: Vascularized Lymph Node Transfer (Vlnt)mentioning
confidence: 99%
“…21 Although the reported cases of secondary lymphedema from harvesting the VLNT is low, it is still the main concern of VLNT. 3,10,15,20,36,37 In a study by Viitanen et al, 20 decrease in lymphatic transport index at the donor leg following harvesting VLNT from the groin were noted, although these patients did not demonstrate any clinical signs of lymphedema such as physical complaints or differences in limb measurement.…”
Section: Assessment and Monitoringmentioning
confidence: 92%